Waist-to-Hip Ratio, but Not Body Mass Index, Is Associated with Testosterone and Estradiol Concentrations in Young Women - Ricardo Mondragón-Ceballos; Mónica Dafne García Granados; Ana Lilia Cerda-Molina; Roberto Chavira-Ramírez; Leonor Estela Hernández-López (International Journal of Endocrinology)
We studied if testosterone and estradiol concentrations are associated with specific female waist-to-hip ratios (WHRs) and body mass indices (BMIs). Participants were 187 young women from which waist, hips, weight, and height were measured. In addition, participants informed on which day of their menstrual cycle they were and provided a 6 mL saliva sample. Ninety-one of them were in the follicular phase and 96 in the luteal phase. Only in the fertile phase of the menstrual cycle we found a significant interaction between testosterone and estradiol affecting WHR (b±s.e.=-0.000003±0.000001; t94=-2.12, adjusted R2=-0.008, P=0.03). Women with the highest levels of both hormones had the lowest WHRs, while women with low estradiol and high testosterone showed the highest WHRs. BMI significantly increased as testosterone increased in female in their nonfertile days.